THE INTEGRATION OF VIRTUAL REALITY (VR), AUGMENTED REALITY (AR) AND GAMIFICATION IN DEVELOPING INTERACTIVE SIMULATIONS FOR THE VISUALISATION OF ABSTRACT CONCEPTS IN SCIENCE EDUCATION - Zulvia Trinova; Parni (Indonesian Journal of Education (INJOE), 2026)
Teaching abstract concepts in science, such as atomic structure, chemical reactions and biological systems, often faces fundamental challenges due to the limitations of conventional visualisation methods, resulting in low levels of conceptual understanding and student motivation. This article aims to outline the integration of Virtual Reality (VR), Augmented Reality (AR), and gamification in developing interactive simulations to visualise these abstract concepts in an immersive and engaging manner. The methods employed include a literature review relevant to the TPACK model, the SAMR model, and Mayer’s multimedia principles. The research findings indicate that VR creates a fully immersive environment for microscopic and macroscopic scientific exploration, whilst AR overlays interactive 3D elements onto real-world contexts; both enhance spatial ability by up to 45% and memory retention by up to 80%. The integration of gamification through badge mechanics, quests, and leaderboards reinforces intrinsic and extrinsic motivation in line with Self-Determination Theory, with a 93% increase in cognitive-emotional-behavioural engagement and an N-gain score of 0.63–0.78 in the Indonesian case study. The synergy of these three technologies, framed by TPACK-SAMR-Mayer, transforms science learning from passive and abstract to active and concrete, preparing students for the Merdeka Curriculum and the Society 5.0 era. Strategic recommendations include TPACK-gamification-based teacher training, the development of an open-source content repository in Indonesian, subsidies for mobile AR devices, and longitudinal research into long-term impacts. This integration marks a paradigm shift towards immersive science education that is personalised, adaptive, and globally competitive.